Evaluation of the Effect of Stem Cell-based Scaffolds on Bone Regeneration and Formation in Maxillofacial Bone Disorders: A Systematic Review and Meta-analysis - Saeed Mehraban; Shirin Zahra Farhad; Mehrdad Barekatain; Ali Salehi; Mina Aghabeigi; Armin Khosravi (International Journal of Scientific Research in Dental and Medical Sciences, 2024)
Background and aim: Tissue engineering has provided many hopes for reconstructing bone lesions. For bone engineering, stem cells are cultured on suitable scaffolds under controlled stimulation conditions with growth factors. A scaffold is a temporary matrix for bone growth that provides a specific environment for tissue development and facilitates cell adhesion, growth, and differentiation. The present study aimed to evaluate the effect of stem cell base scaffolds on bone regeneration and formation in maxillofacial bone disorders. Material and methods: Searching international databases PubMed, Web of Science, Scopus, Science Direct, Web of Knowledge, EBSCO, Wiley, ISI, Elsevier, Embase databases, and Google Scholar search engine based on PRISMA 2020-27-item checklist and keywords Related to the objectives of the study, it was carried out from 2013 to January 2024. The prevalence was equivalent to the rate ratio of bone formation. A model with fixed effect and inverse–variance method was used. All statistical analyses are done using STATA/MP software. v17 was done considering the significance of less than 0.05. Results: Nine studies were selected according to the inclusion criteria. The fixed-effects rate ratio of bone formation meta-analysis showed that ES = 0.39, 95% CI; 0.34-0.45, p-value < 0.001. the test of group differences showed no statistically significant difference between types of stem cells in the rate ratio of bone formation in maxillofacial bone disorders, and all three types have similar findings (p=0.08). Conclusions: All three types of stem cells (DPSCs, ADSCs, BMSCs) used in Maxillofacial Bone Disorders showed similar findings in the ratio of bone formation.